Hematological parameters of sheep and goats fed diets containing various amounts of water hyacinth (Eichhornia crassipes) - Fanta, Yared; Kechero, Yisehak; Yemane, Nebiyu (Frontiers in Veterinary Science, 2024)
A major global barrier to increased animal output is nutrition. The use of aquatic plants, which were previously considered to be waste and needed a lot of labor to eliminate, has recently come to light due to the lack of feed during the dry season in the majority of tropical regions of Africa.The objectives of this study were therefore to see how different dietary Eichhornia crassipise inclusion rates affect the haematological indicators of Ethiopian Doyogena sheep and Woyto-Guji goats. Blood samples were taken from the jugular veins of twelve Doyogena sheep and twelve Woyto-Guji goats in a 2 × 4 randomized crossover design with two animal species, four diets, and four random periods (15 -day adaption period followed by a 7-day experimental diet in each period). The dietary inclusion rates E. crassipise were 0, 25, 50, and 75% that was used as a replacement for commercial concentrate mix diet in the treatment groups. The data was analyzed using the SAS software programme PROC GLM, and Pearson's correlation coefficient was calculated between haematological markers. The haemoglobin (Hb), red blood cell count (RBC), packed cell volume (PCV), mean corpuscular volume (MCH), and mean corpuscular hemoglobin (MCHC) results revealed substantial, RDW-SD, and WBC differences between animal species (P < 0.001). Sheep had greater WBC, Hb, RBC, PCV, RDW-SD, and RDW-CV levels, while goats had higher MCH and MCHC values (P < 0.001). For the analysed haematological measures, the Pearson's correlation coefficient ranged from low to strong in terms of positive and negative associations (P < 0.05). Since all haematological indicators were closer to those of clinically healthy native Ethiopian sheep and goat breeds, feeding water hyacinth to sheep and goats up to a 75% inclusion level in diets without producing sickness may provide a remedy for adverse feed shortages.